Portable electronics device with programmable battery - PLESTID THOMAS LEONARD TREVOR (2013)
A portable electronics device comprises at least one device subsystem, and a programmable battery. The programmable battery is coupled to a power input of the device subsystem and is configured to dynamically adjust a characteristic of the power that is applied to the power input in accordance with a power configuration command that is received at the battery.